Caries experience among adults exposed to low to moderate doses of ionizing irradiation in childhood - the Tinea Capitis Cohort - Yuval eVered; Angela eChetrit; Harold eSgan-Cohen; Tova eAmitai; Jonathan eMann; Hadas eEven-Nir; Siegal eSadetzki; Siegal eSadetzki (Frontiers Media S.A., 2016)
While the impact of therapeutic levels of ionizing radiation during childhood on dental defects has been documented, the possible effect of low doses on dental health is unknown. The study aims were to assess the association between childhood exposure to low-moderate doses of therapeutic radiation and caries experience among a cohort of adults 50 years following the exposure.The analysis was based on a sample of 253 irradiated (in the treatment of Tinea Capitis) and 162 non-irradiated subjects. The DMFT (Decayed, Missing, and Filled Teeth) index was assessed during a clinical dental examination and questions regarding dental care services utilization, oral hygiene behavior, current self-perceived mouth dryness, socio-demographic parameters and health behavior variables were obtained through a face to face interview.An ordered multivariate logistic regression model was used to assess the association of the main independent variable (irradiation status) and other relevant independent variables on the increase in DMFT.Mean caries experience levels (DMFT) were 18.6+7.5 for irradiated subjects compared to 16.4+7.2 for the non-irradiated (p=0.002). Controlling for gender, age, education, income, smoking, dental visit in the last year and brushing teeth behavior, irradiation was associated with a 72% increased risk for higher DMFT level (95% CI 1.19-2.50). A quantification of the risk by dose absorbed in the salivary gland and in the thyroid gland showed adjusted ORs of 2.21 per 1Gy (95% CI 1.40-3.50) and 1.05 per 1cGy (95% CI 1.01-1.09), respectively.Childhood exposure to ionizing radiation (0.2-0.4Gy) might be associated with late outcomes of dental health. In line with the guidelines of the American Dental Association, these results call for caution when using dental radiographs.